Age of acquisition of 299 words in seven languages: American English, Czech, Gaelic, Lebanese Arabic, Malay, Persian and Western Armenian - Łuniewska, Magdalena; Wodniecka, Zofia; Miller, Carol A; Smolík, Filip; Butcher, Morna; Chondrogianni, Vasiliki; Hreich, Edith Kouba; Messarra, Camille; A Razak, Rogayah; Treffers-Daller, Jeanine; Yap, Ngee Thai; Abboud, Layal; et al. (PloS one, 2019)
We present a new set of subjective Age of Acquisition (AoA) ratings for 299 words (158 nouns, 141 verbs) in seven languages from various language families and cultural settings: American English, Czech, Scottish Gaelic, Lebanese Arabic, Malaysian Malay, Persian, and Western Armenian. The ratings were collected from a total of 173 participants and were highly reliable in each language. We applied the same method of data collection as used in a previous study on 25 languages which allowed us to create a database of fully comparable AoA ratings of 299 words in 32 languages. We found that in the seven languages not included in the previous study, the words are estimated to be acquired at roughly the same age as in the previously reported languages, i.e. mostly between the ages of 1 and 7 years. We also found that the order of word acquisition is moderately to highly correlated across all 32 languages, which extends our previous conclusion that early words are acquired in similar order across a wide range of languages and cultures.
Keywords: Culture; Learning; kultura; Language; Humans; věkové faktory; Child; lidé; Infant; dítě; předškolní dítě; kojenec; učení; Age Factors; jazyk (prostředek komunikace); Child, Preschool; Vocabulary; slovní zásoba